Using spatial big data to analyse neighbourhood effects on immigrant inclusion and well-being - Leong, Chan-Hoong (2024)
This paper examines how the social and built environment shapes preference on protectionist immigration policy, generalised trust, and life satisfaction. It seeks to understand the intergroup processes that underpin intergroup contact and acculturation in the neighbourhoods by combining an individual-level survey (n = 1188) with census information on housing resale transactions (as proxy of socio-economic class) and other geospatial points of interest. Analyses of spatial big data revealed that neighbourhoods with a higher density of ethnic minorities and immigrant households are characterised by lower trust and quality of life. In contrast, neighbourhoods with a higher density of immigrant households are associated with a preference for a protectionist immigration policy (mitigated by proximity to community clubs). These environmental factors are associated with the outcome even after controlling for individual-level differences. Importantly, the findings underscore the enduring influence of ethnicity and immigrant identities more than the socio-economic background of the neighbourhood. Intergroup contact alone is insufficient to foster inclusion, especially in locales densely populated with ethnic minorities and immigrant communities. Shared amenities, such as community clubs, were found to play a crucial role in creating a conducive environment for meaninful contact.